Trunk-Pelvis motions and spinal loads during upslope and downslope walking among persons with transfemoral amputation. (11th October 2019) - Acasio, Julian C.; Shojaei, Iman; Banerjee, Rajit; Dearth, Christopher L.; Bazrgari, Babak; Hendershot, Brad D.
Abstract: Larger trunk and pelvic motions in persons with (vs. without) lower limb amputation during activities of daily living (ADLs) adversely affect the mechanical demands on the lower back. Building on evidence that such altered motions result in larger spinal loads during level-ground walking, here we characterize trunk-pelvic motions, trunk muscle forces, and resultant spinal loads among sixteen males with unilateral, transfemoral amputation (TFA) walking at a self-selected speed both up ("upslope"; 1.06 ± 0.14 m/s) and down ("downslope"; 0.98 ± 0.20 m/s) a 10-degree ramp. Tri-planar trunk and pelvic motions were obtained (and ranges-of-motion [ROM] computed) as inputs for a non-linear finite element model of the spine to estimate global and local muscle (i.e., trunk movers and stabilizers, respectively) forces, and resultant spinal loads. Sagittal- (p = 0.001), frontal- (p = 0.004), and transverse-plane (p < 0.001) trunk ROM, and peak mediolateral shear (p = 0.011) and local muscle forces (p = 0.010) were larger (respectively 45, 35, 98, 70, and 11%) in upslope vs. downslope walking. Peak anteroposterior shear (p = 0.33), compression (p = 0.28), and global muscle (p = 0.35) forces were similar between inclinations. Compared to previous reports of persons with TFA walking on level ground, 5–60% larger anteroposterior and mediolateral shear observed here (despite ∼0.25 m/s slower walking speeds) suggest greater mechanical demands on the low back in sloped walking, particularly upslope. Continued characterization of trunk motions and spinal loads during ADLs support the notion that repeated exposures to these larger-than-normal (i.e., vs. level-ground walking in TFA and uninjured cohorts) spinal loads contribute to an increased risk for low back injury following lower limb amputation.